2013
DOI: 10.3390/biom3030514
|View full text |Cite
|
Sign up to set email alerts
|

Lipases Immobilization for Effective Synthesis of Biodiesel Starting from Coffee Waste Oils

Abstract: Immobilized lipases were applied to the enzymatic conversion of oils from spent coffee ground into biodiesel. Two lipases were selected for the study because of their conformational behavior analysed by Molecular Dynamics (MD) simulations taking into account that immobilization conditions affect conformational behavior of the lipases and ultimately, their efficiency upon immobilization. The enzymatic synthesis of biodiesel was initially carried out on a model substrate (triolein) in order to select the most pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…(tpG) and the invertase from Saccharomyces cerevisiae (ISc) 17 . Overall, lipases have a wide industrial impact in the food, pharma and cosmetic sectors but their catalytic potential is far from being fully exploited for the production of commodities or biodiesel [19][20][21] . CaLB (3.1.1.3) is widely employed in the production of fine chemicals for its selectivity but also in the production of esters for body care sector.…”
Section: Functionalization Of Rh and Immobilization Of Enzymes Accordmentioning
confidence: 99%
See 1 more Smart Citation
“…(tpG) and the invertase from Saccharomyces cerevisiae (ISc) 17 . Overall, lipases have a wide industrial impact in the food, pharma and cosmetic sectors but their catalytic potential is far from being fully exploited for the production of commodities or biodiesel [19][20][21] . CaLB (3.1.1.3) is widely employed in the production of fine chemicals for its selectivity but also in the production of esters for body care sector.…”
Section: Functionalization Of Rh and Immobilization Of Enzymes Accordmentioning
confidence: 99%
“…The protocol employing vegetable oil as immobilization medium implies that no enzyme is lost during the procedure because no partition occurs between an aqueous and a solid phase but rather the dissolved protein is adsorbed onto the carrier 21 . In conclusion, RH demonstrated a low affinity towards CaLB when used in aqueous medium, most probably because of its lower hydrophobic nature as compared PS and MA/DVB.…”
Section: Functionalization Of Rh and Immobilization Of Enzymes Accordmentioning
confidence: 99%
“…Lipases are one of the enzyme classes most widely employed in industry, in part because of their potential to work in non-aqueous environments, and they are applied on an industrial scale for the transesterification of fats and oils in the food segment (FERRARIO et al, 2013). To ensure optimal biocatalyst activity and attain high yield reactions, several factors must be taken into consideration, mainly the temperature, water content and the loading of the biocatalyst in the reaction medium (MARTINS et al, 2013;FRIEDRICH et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The optimum temperature of the immobilized lipase was 50 °C, whereas that of the free one was 40 °C. It can be concluded that the immobilization using BFN particles enhanced the thermal stability of lipase, which might be caused by multipoint attachment of the lipase to the support and/or by the hydrophobic interaction [ 31 ].…”
Section: Resultsmentioning
confidence: 99%